Interstellar gas heating by primordial black holes. Issue 3 (1st March 2022) - Takhistov, Volodymyr; Lu, Philip; Gelmini, Graciela B.; Hayashi, Kohei; Inoue, Yoshiyuki; Kusenko, Alexander
Abstract: Interstellar gas heating is a powerful cosmology-independent observable for exploring the parameter space of primordial black holes (PBHs) formed in the early Universe that could constitute part of the dark matter (DM). We provide a detailed analysis of the various aspects for this observable, such as PBH emission mechanisms. Using observational data from the Leo T dwarf galaxy, we constrain the PBH abundance over a broad mass-range, M PBH ∼ 𝒪(1) M ⊙ − 10 7 M ⊙, relevant for the recently detected gravitational wave signals from intermediate-mass BHs. We also consider PBH gas heating of systems with bulk relative velocity with respect to the DM, such as Galactic clouds.